Regime and Periphery in Northern Yemen The Huthi Phenomenon - Salmoni, Barak A. (RAND Corporation, 2010)
For nearly six years, the government of Yemen has conducted military operations north of the capital against groups of its citizens known as "Huthis." In spite of using all means at its disposal, the government has been unable to subdue the Huthi movement. This book presents an in-depth look at the conflict in all its aspects. The authors detail the various stages of the conflict and map out its possible future trajectories.